TFNR2 in Ischemia-Reperfusion Injury, Rejection, and Tolerance in Transplantation - Kouyoumdjian, Araz; Tchervenkov, Jean; Paraskevas, Steven (Frontiers in Immunology, 2022)
Tumor necrosis factor receptor 2 (TNFR2) has been shown to play a crucial role in CD4+ T regulatory cells (CD4+Tregs) expansion and suppressive function. Increasing evidence has also demonstrated its role in a variety of immune regulatory cell subtypes such as CD8+ T regulatory cells (CD8+ Tregs), B regulatory cells (Bregs), and myeloid-derived suppressor cells (MDSCs). In solid organ transplantation, regulatory immune cells have been associated with decreased ischemia-reperfusion injury (IRI), improved graft survival, and improved overall outcomes. However, despite TNFR2 being studied in the context of autoimmune diseases, cancer, and hematopoietic stem cell transplantation, there remains paucity of data in the context of solid organ transplantation. Interestingly, TNFR2 signaling has found a clinical application in islet transplantation which could guide its wider use. This article reviews the current literature on TNFR2 expression in immune modulatory cells as well as IRI and solid organ transplantation. Our results highlighted the positive impact of TNFR2 signaling in solid organ transplantation, especially kidney and islet transplantation. However, further investigation of TNFR2 in all types of solid organ transplantation are required as well as dedicated studies on its therapeutic use during induction therapy or treatment of rejection.